DINAMIKA TERJEMAH AL-QURA’AN BAHASA MADURA: STUDI ATAS TERJEMAH I’RABAN KETERANGAN MADHURAH ATORO’ LIL-JALALAIN (TIKMAL) - Roudlotul Jannah; Maulana Achmad; Mardliyatun Nahdliyah Putri (Mafatih, 2022)
The I’raban translation book in Madhurah Atoro’ Lil-Jalalain description (TIKMAL) is a translation book in Madura language. TIKMAL book was made as one of the critisism from Madura Islamic scholars on another Maduranese translation book that was released before. Some Madura scholars found some gaffes on the previous translation, so a team of some scholars in Madura was made to translate al-qur’an in Madura language, that’s why TIKMAL kitab was made. The question to this study is “what are the background, methodology and implementation of the formation of TIKMAL book in Madura?” To answer this question, approach used was philology theory. The process of analyzing the data was done in three stages: analyzing the physical script, analyzing the text, analyzing using language science. The result was, this study showed that TIKMAL book is a translation book in Madura language and included as a literal translation (harfiah). TIKMAL book was made as one of the critisism from Madura Islamic scholars on another Maduranese translation book that was released before, which is “al-qur’an tarjamah Bahasa Madura”. TIKMAL bool was spread out in Madura, both in islamic boarding school and place to recite alquran in village called langgar. In islamic boarding school, TIKMAL becomes a learning reference source for students.